Human development and capabilities : re-imagining the university of the twenty-first century - Boni, Alejandra.; Walker, Melanie. (Routledge, 2013)
"Globally, universities are the subject of public debate and disagreement about their private benefits or public good, and the key policy vehicle for driving human capital development for competitive knowledge economies. Yet what is increasingly lost in the disagreements about who should pay for university education is a more expansive imaginary which risks being lost in reductionist contemporary education policy. This is compounded by the influences on practices of students as consumers, of a university education as a private benefit and not a public good, of human capital outcomes over other graduate qualities, and of unfettered markets in education. Policy reductionism comes from a narrow vision of the activities, products, and objectives of the University and a blinkered vision of what is a knowledge society. Human Development and Capabilities, therefore, imaginatively applies a theoretical framework to universities as institutions and social practices from human development and the capability approach, attempting to show how universities might advance equalities rather than necessarily widen them, and how they can contribute to a sustainable and democratic society"--